Grounding Pancasila Law as the Future of National Law Basis - Nugroho, Sigit Sapto (Law Research Review Quarterly, 2016)
An independent Indonesia since 1945 is a constitutional state. As a law state, every life of the nation and state must be guided or based on law. In order to realize the ideals of the rule of law, efforts are needed to develop a national law with an Indonesian spirit, which is a law that is built from the process of excavation, discovery and development that is sourced from the values ​​of cultural life, as well as the soul of the people (volkgeist) of Indonesia. Legal development that relies on Indonesian volkgeist is very necessary to create a law that has a personality of Indonesia, namely the development of law which is based on the philosophy and ideology of Pancasila. So that the Pancasila law is able to create justice, order and legal certainty aimed at enhancing the unity and integrity of the nation and state. Normative beliefs in Pancasila are described in eight Pancasila frames which are the spirit, logic and values ​​that make Pancasila meaningful to Indonesia and become a fundamental basis in building the Indonesian legal system. Thus the future national legal basis is Pancasila Law.